Initial investigation of hydraulics engineering for flood mitigation: A case study in Krueng Aceh Sub-watershed. Issue 1 (January 2021) - Saputra, A A; Saputro, D D; Prastica, R M S
Abstract: Problem of flooding in the Krueng Aceh Sub-watershed occurs almost every year, thus, the study is conducted. This article aims at the initial study of flood mitigation investigations in the Krueng Aceh Sub-watershed, which consists of an analysis of existing channel hydraulics and an ideal design plan at the study site for hydrological analysis of the Sub-watershed. In addition to the analysis of channel hydraulics, analysis of the safety factors of existing channel cliffs and plans is also carried out. In addition to flood mitigation in the form of redesigning existing canals, this article proposes the construction of an earth-embankment dam. In the analysis of this existing channel, discharge is obtained by 1098.857 m 3 /s. When compared with the design flood discharge for a period of 100 years, the channel discharge capacity cannot accommodate flood discharge. With the redesign of the channel, the storage capacity can accommodate the flood discharge with a safety factor of 2.804, greater than the existing channel of 2.711. Earth-embankment dam is proposed with a safety factor of 3.497. Further studies need to be done flood routing to find out how much the contribution of the dam reservoir to the reduction of flooding in the study area.